Reflections on medical student evaluations of a public health clerkship - Rahma, Azhar T.; Ádám, Balázs; Abdullahi, Aminu S.; Sheek-Hussein, Mohamud; Shaban, Sami; AlShamsi, Mouza; AlKhori, Salama; Nauman, Javaid; Grivna, Michal (Frontiers in Public Health, 2023)
Introduction The COVID-19 pandemic demonstrated the need for skilled medical practitioners in public health, and outbreak investigations. The College of Medicine and Health Sciences at the United Arab Emirates University (UAEU) introduced a clerkship in public health constituting theoretical and practical sessions to 5th year medical students in 2015. The aim of this study is to explore the satisfaction of the students with the public health clerkship which is crucial for the assessment and reformation of the taught curriculum. Methods A cross-sectional, post-evaluation analysis was conducted from the period 2015–2022. The evaluation questionnaire was conducted via an online university system. The survey contained 5 themes: pre-course instructions, structure of the clerkship, academic staff, activities, and learning outcomes. Ethics approval was secured from the Social-IRB of the UAEU. We used SPSS version 26 to analyze the data using independent t-test and ANOVA. Results One hundred and seventy four students (27.4% response rate) participated in the study. Overall, the students had an average satisfaction score of 2.86 out of 4. The majority of the students reported having a good understanding of public health (93.7%), improving their oral presentation skills (91.2%), and developing new skills (87.2%). Furthermore, more than 9 in 10 students (96.1%) reported that the program expanded their knowledge, skills, and confidence. The mass (90.2%) of students agreed that the clerkship content was covered in sufficient depth, majority of the students agreed that they had received enough information about the clerkship before it started (74.6%), majority of the students agreed that the faculty were interested in their personal development (86.1%) The students who completed the clerkship prior to the COVID-19 pandemic had a statistically significant (P = 0.02) higher average rating (72.8%) than students who completed the clerkship during the pandemic (71.1%). Discussion Medical students at the UAEU were satisfied with the activities and delivery of the public health clerkship and found it rewarding. Conducting needs assessment and proposal writing provided them with the knowledge, skills, and confidence to conduct research in their career. These findings may be useful in helping and support other institutes to plan and develop a clerkship in the public health.